2019
DOI: 10.1253/circj.cj-18-0700
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy-Associated Plasma Protein-A Accelerates Atherosclerosis by Regulating Reverse Cholesterol Transport and Inflammation

Abstract: Background:Recent studies have suggested that pregnancy-associated plasma protein-A (PAPP-A) is involved in the pathogenesis of atherosclerosis. This study aim is to investigate the role and mechanisms of PAPP-A in reverse cholesterol transport (RCT) and inflammation during the development of atherosclerosis. Methods and Results:PAPP-A was silenced in apolipoprotein E (apoE −/− ) mice with administration of PAPP-A shRNA. Oil Red O staining of the whole aorta root revealed that PAPP-A knockdown reduced lipid ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…Pregnancy-associated plasma protein A (PAPPA) has served as an indicator of cardiovascular events, and PAPPA promoted the expression of inflammatory markers, thus triggering atherosclerosis. 16,17 In addition, PAPPA also participated in the regulation of proliferation and apoptosis of ox-LDL-treated VSMCs, 10 whereas the mechanism of PAPPA action in VSMCs is not been completely understood.…”
Section: -(4 5-dimethylthiazol-2-yl)-2 5-diphenyltetrazolium Bromimentioning
confidence: 99%
“…Pregnancy-associated plasma protein A (PAPPA) has served as an indicator of cardiovascular events, and PAPPA promoted the expression of inflammatory markers, thus triggering atherosclerosis. 16,17 In addition, PAPPA also participated in the regulation of proliferation and apoptosis of ox-LDL-treated VSMCs, 10 whereas the mechanism of PAPPA action in VSMCs is not been completely understood.…”
Section: -(4 5-dimethylthiazol-2-yl)-2 5-diphenyltetrazolium Bromimentioning
confidence: 99%
“…After forming an obligate heterodimer with retinoid X receptor, LXRα binds to LXR-response elements in the promoter of ABCA1 and ABCG1 genes to stimulate their transcription 49 . Studies from our group and others have revealed that angiopoietin-1, pregnancyassociated plasma protein-A, and homocysteine inhibit ABCA1-and ABCG1-dependent cholesterol efflux from lipid-loaded macrophages and aggravate atherosclerosis in apoE −/− mice by downregulating LXRα expression [50][51][52] . As a pleiotropic miRNA, miR-155-5p is linked to metabolic diseases, such as diet-induced obesity 53 and diabetes 54 .…”
Section: Discussionmentioning
confidence: 85%
“…There is no parameter to clearly show the diagnosis and activity of BD. 8 This study showed that neopterin and hsCRP increased in Behçet 0 s patients, while PAPP-A did 20 Biomarkers such as hsCRP are also used to assess the contribution of inflammation in the pathophysiology of atherosclerosis and to predict primary cardiovascular risks. 21 In a study between pregnant Behçet's patients and healthy pregnant women, no significant difference was found between PAPP-A levels.…”
Section: Discussionmentioning
confidence: 96%
“…It is known that PAPP‐A levels elevate in ruptured plaques and PAPP‐A trigger thrombotic events. Some investigators suggested PAPP‐A as a new marker for acute coronary syndrome 20 . Biomarkers such as hsCRP are also used to assess the contribution of inflammation in the pathophysiology of atherosclerosis and to predict primary cardiovascular risks 21 .…”
Section: Discussionmentioning
confidence: 99%